12 Myocardial viability in preserved or mildly impaired left ventricular function prior to revascularisation – findings from a 3 year experience. (26th April 2015) - Douglas, H; Cole, B; Soong, CM; Harbinson, M; Horan, P; Dixon, LJ; Johnston, N
Abstract : Background: Viability assessment prior to revascularisation at our institution is largely requested for patients with severely impaired left ventricles (LV). This study however aims to review the outcomes of those patients with preserved or mildly impaired LV function who underwent cardiac magnetic resonance imaging (CMR) for assessment of viability prior to revascularisation and to evaluate its use in this group. Methods: All patients undergoing CMR to assess viability prior to coronary artery revascularisation were identified and included from January 2011 until June 2013. Results: Viability assessments were undertaken in 256 patients who were referred for revascularisation by either percutaneous coronary intervention (PCI) or surgery. Of these 71 (27.7%) were found to have preserved or mildly impaired LV function, defined by an ejection fraction (EF) greater than 45% (72% male, mean age 66 ± 12.8 years). Adenosine stress perfusion was performed in 25.4%. Twenty four percent of patients were turned down for revascularisation. Mean LV measurements within groups were as follows: EF CABG 56.67 ± 7.58%, PCI 57.41 ± 8.58%, medical management 59.4 ± 19.65% (p = 0.58), LVEDV CABG 87.74 ± 19.37 mls, PCI 85.22 ± 20.62 mls, medical 80.41 ± 16.14 mls (p = 0.47). The number of non-viable segments within each group was: CABG 2.15 ± 1.99, PCI 2.15 ± 2.13 and medical 2.41 ± 2.06 (p = 0.90). The nonviable segments were in LAD territory in: CABG 22.2%, PCI 33.3% and medical 29.4% (p = 0.66). Median follow up was 2.4 years. Outcome data was follows; MACE: CABG 14.8%, PCI 7.4% and medical 11.8% (p = 0.69); death: CABG 11.1%, PCI 7.4%, with no reported deaths in the medical management group (p = 0.37); revascularisation: CABG 3.7%, PCI 11.1% and medical 11.8% (p = 0.53). Conclusions: Viability assessment by CMR has not been shown to have a significant impact on the management of patients with preserved or mildly impaired LV. We propose that stress perfusion for assessment of ischaemia would improve the utility of CMR in this group.